The Relationship Between Diabetes Burnout Syndrome and Quality of Life in Patients with Diabetes Mellitus - Azizah Nur Oktafiyah; sri sudarsih; Binarti Dwi Wahyuningsih (Journal of Health Empowerment and Interprofessional Practice, 2025)
Background of study: Diabetes mellitus is a chronic non-communicable disease characterized by elevated blood sugar levels that can affect a person’s overall quality of life. A significant factor influencing this condition is diabetes burnout syndrome, which impacts how patients manage their illness and experience their daily lives.Aims and scope of paper: This research sought to explore the association between diabetes burnout syndrome and the quality of life among diabetic individuals.Methods: The research used a correlational analytical method with a cross-sectional design. The sample included 38 respondents who met the inclusion and exclusion criteria. Data were analyzed using the Spearman Rho test. Result: The findings revealed that most participants experienced a moderate level of diabetes burnout, and 31 participants (86.1%) reported a moderate quality of life. The statistical analysis showed a significant negative correlation between burnout and quality of life, with a ρ-value of 0.002 and a correlation coefficient of -0.496. This indicates that as diabetes burnout increases, the quality of life tends to decrease. Conclusion: In conclusion, diabetes burnout significantly affects patients by reducing their quality of life, potentially leading to issues such as poor treatment adherence, increased risk of complications, and various physical, emotional, social, and environmental challenges.